Atopic dermatitis/Dermatitis herpetiformis. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2018)
Atopic dermatitis and dermatitis herpetiformis (Duhring) are different diseases sharing an intense itch. The former is the most frequent infantile skin disease whereas the latter is rather rare. Atopic dermatitis (AD) can be easily diagnosed whereas dermatitis herpetiformis (DH) is usually diagnosed many months after its onset. Although the two diseases have different clinical features, in particolar cases the differential diagnosis can be hardly made.